Prophylaxis and Correction of Reading Difficulties in Education of Elementary-School Children - Iordanov K. B. (PH "Sreda", 2021)
The monograph examines the issues of prevention and correction of difficulties in learning to read, caused by the so-called dyslexia - a violation of the ability to read - in children of primary school age. The diagnostic and advisory function of the primary school teacher and his ability to support children with reading problems by recognizing the corresponding symptoms in time is updated. It examines how students with specific learning difficulties, manifested by symptoms of dyslexia, cope with their problem and whether they can be helped in the practice of primary school.
Keywords: особые образовательные потребности; диагностика; special educational needs; дислексия; терапия; индивидуальные возможности; dyslexia; diagnosis; therapy; individual opportunities